The theory of sound - Rayleigh, John William Strutt (Dover, 1945)
"Unabridged republication of the second revised and enlarged edition of 1894."--verso t.p.; Bibliographical footnotes. Bibliography: v. 1, p. xxx-xxxii.; The book sums up previous research and offers original contributions of Lord Rayleigh. It is, therefore, not only a reference book, but a book of great practical utility for all readers concerned with scientific aspects of sound. Volume 1 covers harmonic vibrations, systems with one degree of freedom, vibrating systems in general, transverse vibrations of strings, longitudinal and torsional vibrations of bars, vibrations of membranes and plates, curved shells and plates, and electrical vibrations. Volume II covers aerial vibrations, vibrations in tubes, reflection and refraction of plane waves, general equations, theory of resonators, Laplace's functions and acoustics, spherical sheets of air, vibration of solid bodies, and facts and theories of audition